8 Implementasi Moderasi Beragama dalam Pembinaan Baca Al-Qur’an Perspektif Pendidikan Islam di Desa Cukanggenteng Kecamatan Pasirjambu RW 04 Sindangsari - Agustini, Triani; Rizqi N.U, Firdiani; Nurfazri, Arini (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
The importance of reading the Qur’an properly and correctly, so that reading the Qur’an well is one of the conditions for becoming a prayer priest, namely not saying the wrong word (reading the Qur’an) so that it damages the meaning when reading al-Fatihah and not an ummi, that is, cannot read al-Fatihah properly. The purpose of this study was to find out how the implementation of religious moderation in fostering Al-Qur’an reading in Cukanggenteng Village, Pasirjambu District, RW 04 Sindangsari. The service method carried out for the Sindangsari Hamlet Community is following the cycle of the Sisdamas KKN stages of UIN Sunan Gunung Djati Bandung, which consists of cycle I to cycle IV. KKN participants make observations first with the local community as an effort to find out how far the teaching has been delivered. The results showed that the implementation of religious moderation in fostering Al-Qur’an reading from an Islamic religious perspective in Cukanggenteng Village, Pasirjambu District RW 04 Sindangsari contained activities which included reading the Al-Quran and iqro, memorizing Al-Quran surahs, and learning about the Prophet and His Apostle. Keywords: dedication, KKN, religion